Prevalence and risk factors associated with alcohol consumption among indigenous people in Sabah Borneo Island - Rusdi Abd Rashid; Mohd Nazri Mohd Daud; Rhanye Mac Guad; Siew, Hua Gan; Wan Azlinda Irnee Wan Husin; Nelbon Giloi; Mahmoud Danaee; Mas Ayu Said; Liew, Constance Sat Lin; Ramy Bulan; Abdul Marsudi Manah; Azirah Hashim; et al. (Wiley-Blackwell Publishing Ltd, 2021)
Objectives In this study, we aimed to determine the prevalence and risk factors of alcohol use among a cohort of population in Sabah. Design This is a prospective, cohort study involving rural community residents. Setting Rural community resident at Bingkor, Keningau, Sabah. Participants 363 individuals aged 13 years old and above. Intervention Community-based participatory research to determine the prevalence and risk factors associated with alcohol use. Main outcome measures Measurement of alcohol use using Alcohol Use Disorders Identification Test (AUDIT) and assessment of psychiatric morbidity using Mini International Neuropsychiatric Interview (MINI) questionnaires. Results Most alcohol drinkers aged between 36-45 years old, followed by 26-35 years old and 46-55 years old. Interestingly, there are almost similar female to male ratio. Most were Kadazan-Dusun ethnic, non-Muslims, and married. Although only less than a third of the participants received tertiary education, the majority were working. Based on the findings, being a male, non-Muslim and having an obsessive-compulsive disorder (OCD) (current) posed a significantly higher risk of alcohol consumption. Conclusion A worryingly high prevalence of hazardous alcohol consumption among the locals is reported. There is a need for population-wide intervention towards preventive measures based on the identified risk factors for hazardous alcohol use.